Hypnobirthing as an Effort to Reduce Anxiety in Pregnant Women: A Literature Review - Yulizawati Yulizawati; Hardisman Hardisman; Lulisa Desrama Tasya (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: Pregnancy is a physiological state, they may cause anxiety because of the various discomforts that the mother feels during pregnancy. Hypnobirthing is a birthing method that uses hypnotherapy techniques to reduce anxiety and increase comfort during the birthing process. This technique is believed to be able to increase the mother's control over the birth process, as well as improve the quality of childbirth. Purpose: The purpose of this study was to find out how the application of hypnobirthing techniques can reduce anxiety in pregnant women Methods: This research method was a literature review study. Journal searches were carried out by applying online database such as Pubmed database, Garuda Portal, ScienceDirect and Google scholar. Articles were selected based on inclusion and exclusion criteria. Results: The analysis was carried out on 21 research articles. It was found that hypnobirthing give comfort and confidence in the body's abilities. The application of Hypnobirthing techniques can and effectively reduce the anxiety level of pregnant women and even eliminate the anxiety during pregnancy. Conclusion: The influence of hypnobirthing is useful in overcoming anxiety during pregnancy.